Major League Baseball Marketing Strategies and Industry Promotion Approaches - Chen, Meihong; Su, Fuzhi; Tai, Feng (Frontiers in Psychology, 2022)
The sport of baseball is one of the chief pillars of the American sports industry. Major League Baseball (MLB) is the earliest professional sports league in the United States, and has long since formulated comprehensive marketing strategies and global industry promotion approaches, which have proved to be exceptionally successful. Accordingly, study of MLB's marketing strategies and industry promotion approaches will have important significance to the development of baseball in China and the establishment of an industry chain. This paper employed the literature consultation method, comparative analysis method, and inductive method to analyze MLB's localized marketing strategies and development trends in China, and obtained the following insights concerning MLB's promotion and industry development efforts in China: (1) MLB has used a "family sport" concept to promote baseball culture, and employed a project culture approach to promote the universal spread of the sport of baseball. (2) MLB has sought to join baseball with school sports as a means of developing baseball talent. (3) MLB has promoted its brand, built up a baseball industry chain, and performed comprehensive market cultivation. (4) MLB has strengthened baseball infrastructure and encouraged baseball's rapid development.